Gift and Glory: Two Narratives of a Safavid Mission in Venice - Rokhgar, Negar (Material Culture Review / Revue de la culture matérielle)

(untitled) (Cape Breton University Press, 2024)
The gift of a velvet with repeating patterns of the Virgin Mary nursing Christ (Madonna del Latte) from Shah Abbas of Safavid Persia to the Republic of Venice is often interpreted as the embodiment of the Shah’s two-fold political and commercial motivations in pursuing his transcultural allegiance with Venice against the Porte. This paper explores the Shi’a Safavid iconography of the biblical imagery on this velvet and rereads it as a Safavid attempt in defining commonality across cultures through visual media. This vision differs significantly with the Venetians’ perception of the Shah’s luxurious gifts and letters, which is reflected in Gabriele Caliari’s painting of the Safavid reception by Doge Grimani in 1603, in Palazzo Ducale, Venice. The paper analyzes the two visions of the Safavids and the Venetians in a comparative study of the period’s textual and visual materials. It explores how the gifts such as the Madonna del Latte velvet facilitated diplomatic negotiations with Christian Europe, whereas painted representations such as Caliari’s reveal much about the perception of cultural difference in early modern courts.